Detection of human herpesvirus 6 DNA and chromosomal integration after allogeneic hematopoietic stem cell transplantation: A retrospective single center analysis. Issue 3 (8th May 2022) - Berneking, Laura; Both, Anna; Langebrake, Claudia; Aepfelbacher, Martin; Lütgehetmann, Marc; Kröger, Nicolaus; Christopeit, Maximilian
Abstract: Introduction: Human herpesvirus 6 (HHV‐6) can reactivate after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) and may be associated with significant morbidity and mortality. Methods: The epidemiology of HHV‐6 infections and their impact on outcome after allo‐HSCT were retrospectively analyzed in 689 adult allo‐HSCT recipients (January 2015–December 2018). Chromosomal integration of HHV‐6 (ciHHV‐6) in the donor was retrospectively investigated to critically evaluate antiviral treatment strategies. Results: HHV‐6 DNA in any specimen was found in 89 patients. HHV‐6 infections (encephalitis (one), gastroenteritis (44), dermatitis (two), hepatitis (one), or pneumonitis (five)) were diagnosed in 53/689 patients (7.7%). Elevated levels of HHV‐6 DNA were found in 38 patients (5.5%). ciHHV‐6, analyzed in patients with HHV‐6 viral loads ≥10 4 copies/ml, was identified in four patients (10/38 patients; 10.5%). Two of those displayed copy numbers of HHV‐6 ranging from ≥2 × 10 5 to 2.5 × 10 6 copies/ml (HHV‐6A). Here, ciHHV‐6 was integrated into donor and not into the patients' cells. In this series of allo‐HSCT recipients, 10.5% of patients with blood viral loads of HHV‐6 showed ciHHV‐6. Conclusion: Screening of the donor for ciHHV‐6 before initiation of antiviral therapy is recommended. Abstract :